Comparison of the Effectiveness of Classical and Single-knot Fascia Closure Methods in Reducing Pain and Tenderness in the Incision Area After Cesarean Section: A Prospective Cohort Study - Atilgan, Remzi; Pala, Sehmus; Haliscelik, Mesut Ali; Senocak, Ahmet; Cim, Bunyamin (Turkiye Klinikleri, 2023)
Objective: We compared the effects of single-knot fascia closure technique and classical fascia closure technique on postoperative pain in fascia closure. Material and Methods: In this prospective cohort study, 80 term non-obese pregnant women who had no complicated pregnancy and no additional disease, and who were planned for elective cesarean section were included in the study. Classical fascia closure method was applied to one group (n=40) and single-knot fascia closure method was applied to the other group (n=40). In the single-knot fascia closure technique, the suture was threaded down from the upper part of the right fascia corner and the needle was removed from the lower part of the fascia upwards, approximately 0.5 cm behind the left fascia corner. In the classical fascia closure technique, the fascia was closed continuously. Pain was evaluated with visual analogue scale (VAS) at 8(th), 24(th) hours, and 3(rd) months postoperatively. The cases were followed up for the development of infection, hematoma, seroma, and hernia at the wound site within 3 months postoperatively. Results: Wound infection, seroma, hematoma, and hernia did not develop in the postoperative period in both groups. However, VAS values at the 8(th) and 24(th) hours and 3(rd) months were significantly lower in the group in which the single knot fascia closure method was applied. Conclusion: The single-knot fascia closure method is an effective and reliable method in reducing postoperative pain after cesarean section.
Keywords: Cesarean section; postoperative pain; single-knot fascia closure; abdominal fascia